On Heterogeneus, Multidimensional Unconverntional Reservoir Ecosystems - Nimmagadda, Shastri; Dreher, Heinz; Noventianto, A.; Mustaffa, A.; Parapaty, H. (EAGE, 2013)
Worldwide conventional resources are on declining trend. Alternate resources are unconventional sources. Volume of datasets exists in unconventional resources, but they are neither evaluated nor unknown. They are even unaccounted for during drilling campaigns and evaluations. Because of exploration and development setbacks, productibility, recovery costs and environmental concerns, exploitation of unconventional resources is held up on global market. In order to address these issues, authors propose, multidimensional and heterogeneous, data warehousing and mining approach, supported by ontology. Data integration and exploring multiple connections among attributes of multiple dimensions of unconventional petroleum ecosystems (of different geographic, geological and production regimes) are needed. Authors attempt to make use of ontologies, written for multiple dimensions including periodically (longitudinal dimension) and geographically (distantly, lateral dimension) varying dimensions, within an unconventional resource basin. The proposed methodology is robust and can resolve issues associated with organization of unconventional resources and extend help to technology adaptation. The proposed methodology can be applied in any basin for all unconventional reservoir ecosystems worldwide.